Relationship of Dropout and Psychopathology in a High School Sample in Mexico - Chalita, Pablo J.; Palacios, Lino; Cortes, Jose F.; Panza, Kaitlyn E.; Landeros-Weisenberger, Angeli; Bloch, Michael H. (Frontiers in Psychiatry, 2012)
School dropout has significant consequences for both individuals and societies. Only 21% of adults in Mexico achieve the equivalent of a high school education. We examined the relationship between school dropout and self-reported psychiatric symptoms in a middle school in a suburb of Mexico City. We used binomial logistic regression to examine the odd ratio of school dropout associated with student’s self-reported psychopathology. Two-hundred thirty seven students participated in the study. Psychosis (Odds Ratio (OR)=8.0 (95% Confidence Interval (CI): 1.7-37.2), depression (OR=4.7 (95% CI: 2.2-9.7)), tic disorders (OR=3.7 (95%CI: 1.4-9.5)), ADHD (OR=3.2 (95%CI:1.5-6.4)), and social phobia (OR=2.6 (95%CI: 1.2-5.8)) were associated with increased risk of school dropout after controlling for age and gender as covariates. Our study suggested that students’ self-reported psychopathology is associated with increased school dropout in Mexico.